Taxonomic revision of the owlfly genus Glyptobasis McLachlan, 1873 (Neuroptera: Ascalaphidae) from India and its adjacent countries - Suryanarayanan, Thangalazhi Balakrishnan; Ábrahám, Levente; Bijoy, Chenthamarakshan (Zootaxa, 2024)
Species of the owlfly genus Glyptobasis McLachlan, 1873 from India and its adjacent countries are revised. Two species, Glyptobasis dentifera (Westwood, 1847) and Glyptobasis nigrifrons Kimmins, 1949 are redescribed based on freshly collected specimens from Kerala, India. The status of all Glyptobasis species reported from the Oriental region is revised. Lectotypes and paralectotypes of Glyptobasis dentifera (Westwood, 1847 and Glyptobasis spinicornis van der Weele, 1909 are currently designated after comparison to the type specimens in different collections. Glyptobasis denticornis Kimmins, 1949 (syn. n.) is a new junior synonym of Glyptobasis spinicornis van der Weele, 1909. A key to six species of Glyptobasis is provided. Based on the relevant literature, the known distribution of each species and the flight period of the imagos are given.